To censor or not to censor: (in)appropriate language in Croatian film translation - Ščukanec, Aleksandra (2013)
In this paper we will present our research on the attitudes towards censorship in film translation in Croatia and its perception among two different groups of informants. In the first group there were 54 students of a foreign language or foreign languages (mainly of English and German), who are at the same time likely to become translators, and 4 professional translators, whereas the second group comprised 42 informants of various professions. Apart from occupation, main parameters taken into consideration in the analysis of the results obtained from the questionnaire were age and gender. Our analysis has shown that most informants from both groups are “irritated” with a practice which is commonly used in Croatia regarding translation of inappropriate language, primarily swearwords. But these two groups have a rather different interpretation when it comes to inappropriate language, social taboos or politically correct terms. The informants from the first group are more prone to use “mild expressions”, euphemisms and politically correct terminology. Many say that the written word has a certain weight and that they would not like their names to stand next to a translation which abounds in what they consider inappropriate language. In their answers we noticed that they already see themselves closer to the role of a translator than of a recipient (viewer). The informants from the second group opt for translations which are not subjected to censorship and claim to like some programmes on commercial television(s) or in cinemas more because there “they are not afraid” to translate what is said. They find these translations more plausible and true to the original. However, there were certain gender differences: females are in most cases a bit reluctant concerning usage of swearwords and sometimes see them too offensive when they are written. But there are also some considerably different attitudes among informants from the same group which will be discussed in our presentation
Projekt MZOS
ENG